Parent's Experience in Caring for Mentally Retarded Children in the Lovely Hands Community of Sunter Lake Parish - Febriyanti, Patricia; Anggraeni, Lina Dewi; Kusumaningsih, Indrianti (Jurnal Keperawatan Profesional (KEPO), 2025)
Mentally retarded children are children who are retarded in terms of intelligence, physical, social and emotional so that they require special treatment to achieve optimal development and skills. Parents have a great responsibility for special care for mentally retarded children and helping children learn new things, fulfill basic needs, practice independence, self-care and life skills. This study aimed to explore parents’ experiences in caring for mentally retarded children in the Lovely Hands Community, Sunter Lake. This study used a qualitative method with a descriptive phenomenological approach. Data were collected through in-depth interviews and the main instrument of this study was the researcher. The tools used were a tape recorder, interview guide, and field notes. The data analysis technique was Colaizzi’s method. This research involved five participants. The analysis resulted in six themes: 1) The initial phase of knowing their child has special needs (mentally retarded), 2) The support that mentally retarded children get from the family and the surrounding environment, 3) The phase of care provided for mentally retarded children, 4) Concern for the future of mentally retarded children, 5) The family's hope for their retarded children to be able to live independently and get a job, 6). The meaning of patience and gratitude experienced while caring for mentally retarded children. Researchers suggest that there should be a collaboration between parents and educators in the Lovely Hands Community to train these children. Parents can become therapists at home and apply what has been taught in the community.